Rice SPL10 positively regulates trichome development through expression of HL6 and auxin‐related genes. Issue 8 (4th August 2021) - Li, Jinjie; Tang, Bo; Li, Yingxiu; Li, Chenguang; Guo, Minjie; Chen, Haiyang; Han, Shichen; Li, Jin; Lou, Qijin; Sun, Wenqiang; Wang, Peng; Guo, Haifeng; et al.
Abstract: Trichomes function in plant defenses against biotic and abiotic stresses; examination of glabrous lines, which lack trichomes, has revealed key aspects of trichome development and function. Tests of allelism in 51 glabrous rice ( Oryza sativa ) accessions collected worldwide identified OsSPL10 and OsWOX3B as regulators of trichome development in rice. Here, we report that OsSPL10 acts as a transcriptional regulator controlling trichome development. Haplotype and transient expression analyses revealed that variation in the approximately 700‐bp OsSPL10 promoter region is the primary cause of the glabrous phenotype in the indica cultivar WD‐17993. Disruption of OsSPL10 by genome editing decreased leaf trichome density and length in the NIL‐ HL6 background. Plants with genotype OsSPL10 WD‐17993 / HL6 generated by crossing WD‐17993 with NIL‐ HL6 also had fewer trichomes in the glumes. HAIRY LEAF6 ( HL6 ) encodes another transcription factor that regulates trichome initiation and elongation, and OsSPL10 directly binds to the HL6 promoter to regulate its expression. Moreover, the transcript levels of auxin‐related genes, such as OsYUCCA5 and OsPIN‐FORMED1b, were altered in OsSPL10 overexpression and RNAi transgenic lines. Feeding tests using locusts ( Locusta migratoria ) demonstrated that non‐glandular trichomes affect feeding by this herbivore. Our findings provide a molecular framework for trichome development and an ecological perspective on trichome functions. Abstract : The rice transcription factor SPL10 regulates trichome development by regulating the expression of HAIRY LEAF 6 and hormone‐related genes. Moreover, feeding tests using locusts demonstrated that trichomes offer a physical defense against herbivore insects. These observations provide a molecular framework for trichome development and an ecological perspective on trichome functions.